Worse than communism? Discursive anti-gender mobilizations in Lithuania - Buschmann, Dovainė (Information & Media, 2018)
Without doubt, anti-gender struggles in Lithuania are an essential part of a broader transnational tendency to promote tradition and religion over equality, to discredit the European Union as a place of moral decline, to criticize gender studies as an academic discipline etc. However, some aspects of anti-gender mobilization in this state are locally embedded and historically determined. The aim of this article is to analyze patterns of argumentation and implicit assumptions on the term gender as a conceptual analogy of Communism. Hence, the the focus of this paper is on the following questions: how is the analogy between genderism and Communism constructed in the public discourse in Lithuania? Why is this comparison a successful strategy of anti-gender mobilization? The analysis is based on an intensive reading and an interpretation of selected texts that explicitly tackle the analogy between gender equality policies and Communism.Keywords: gender, anti-genderism, communism, discourse